Peran Strategi Human Resources Business Partner (HRBP) dalam Mengatasi Praktik Talent Hoarding untuk Membangun Internal Marketplace yang Lebih Efektif. (Study kasus : Pada PT Smartfren Telecom – Medan Branch): Penelitian - Ribka Yosepha Simanjuntak; Wita Efalina Simangunsong; Siska Aminarti Sirait; Jhon Cristmas Damanik; Rotua Sidauru (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to conduct an in-depth analysis of the Human Resources Business Partner (HRBP) strategies in addressing talent hoarding practices to build a more effective internal marketplace at PT Smartfren Telecom – Medan Branch. Talent hoarding, defined as managers’ tendency to retain high-potential employees exclusively within their own units, often restricts talent mobility, limits cross-department competency distribution, and reduces organizational agility in responding to business demands. Using a case study approach, this research examines how HRBPs perform their roles as strategic partners, change agents, operational experts, and employee champions in designing talent mobility policies, managing leadership resistance, and developing a more transparent, measurable, and competency-based internal talent movement system. The study also explores HRBP initiatives in fostering a collaborative culture, increasing leaders’ readiness to share talent, and utilizing HR analytics for talent mapping and workforce planning. The findings are expected to offer theoretical and practical insights into how HRBP strategies enhance internal marketplace effectiveness, accelerate employee career development, and strengthen overall organizational resilience.